Perancangan Sistem Informasi Manajemen Organisasi Karang Taruna GMS12 Berbasis Website Menggunakan Metode Agile - Muhammad Aqil Pahluvi; Heri Haerudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
Karang Taruna GMS12 is a youth organization engaged in social activities and organizational financial management. However, its administrative processes are still conducted manually, particularly in activity documentation and financial recording, resulting in unintegrated data, limited accessibility, and lack of transparency. This study aims to design and develop a web-based management information system to improve the effectiveness and efficiency of organizational management. The system development method used is Agile, which allows flexible and adaptive development based on user needs. The research stages include analysis of the existing system, system design, development, and testing using Black Box Testing. The result of this study is a web-based management information system capable of integrating activity and financial data. The system is expected to enhance administrative efficiency, financial transparency, and support the professionalism of the organization.